Microhardness of Al2O3 nanoparticles added YBa2Cu3O7-delta superconductor prepared using auto-combustion reaction - Suan, M.S.M.; Johan, M.R. (Maney Publishing, 2014)
The effects of Al2O3 nanoparticles on the phase formation, microstructure and microhardness of YBa2Cu3O7-delta superconductor prepared by citrate-nitrate auto-combustion reaction were investigated. In this study, YBa2Cu2O7-delta precursor gels containing different compositions of Al nitrate varied from 0.02 to 0.10 mol were continuously heated at 250 degrees C before automatically combusted into very fine ashes. Calcination process at 900 degrees C for 1 h has transformed these ashes into sample powders. The XRD and EDX results revealed that Al2O3 nanoparticles were yielded as separate phase from YBa2Cu3O7-delta. The nanoparticles were observed homogeneously distributed in <= 0.06 mol samples while agglomerated along YBa2Cu3O7-delta grain boundaries in other samples. The 0.06 mol sample has the highest microhardness compare with the other samples. The Al2O3 nanoparticles by <= 0.06 mol compositions were effectively acted as reinforced phase which prevent further dislocation movements of YBa2Cu3O7-delta grains. As for = 0.06 compositions, agglomeration of Al2O3 nanoparticles may introduce ductility.